2006
DOI: 10.1063/1.2345109
|View full text |Cite
|
Sign up to set email alerts
|

Phase space quantum mechanics - Direct

Abstract: Nonassociative structure of quantum mechanics in curved space-time Conventional approach to quantum mechanics in phase space, ͑q , p͒, is to take the operator based quantum mechanics of Schrödinger, or an equivalent, and assign a c-number function in phase space to it. We propose to begin with a higher level of abstraction, in which the independence and the symmetric role of q and p is maintained throughout, and at once arrive at phase space state functions. Upon reduction to the q-or p-space the proposed form… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The interested reader is invited to consult the original papers [1,2] for further details. In the framework of the proposed formalism, the extended Lagrangian can be written as…”
Section: The Integrals Of Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interested reader is invited to consult the original papers [1,2] for further details. In the framework of the proposed formalism, the extended Lagrangian can be written as…”
Section: The Integrals Of Motionmentioning
confidence: 99%
“…Here and will be considered as independent -number operators on the integrable complex function ( , ). One of the key assumptions of extended phase space quantization [1,2] is the differential operators and commutation brackets for and borrowed from the conventional quantum mechanics as follows:…”
Section: The Integrals Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each alternative has its own Wigner-type evolution equation which, if Taylor-expanded in powers of the Planck constant, its zeroth order term is the classical Liouville equation. More striking is the fact that for the nD simple harmonic oscillators, Wigner's evolution equation is exactly equation (2.1) and is the phase space transformation of Schroedinger equation for quadratic potentials[7].…”
mentioning
confidence: 99%
“…Carroll [10] has shown that there are generalized quantum theories for which the quantum potential depends on the wave function. Using the extended phase space formulation of quantum mechanics [11,12,13], Nasiri [9] has shown that in the Wigner representation of phase space quantum mechanics [14] the quantum potential is removed from the dynamical equation of a particle in linear and harmonic potentials keeping the Hamilton-Jacobi equation form invariant. It seems that the Husimi representation could be another candidate to release the quantum potential.…”
Section: Introductionmentioning
confidence: 99%